The Effectiveness Of Writing The Letter Of Gratitude Technique In Reducing The Stress Level Of Islamic Boarding School Student - Miftahul Khaer; Ahmad Yasser Mansyur; Ahmad Ridfah; Andi Ahmad Ridha (Psikis : Jurnal Psikologi Islami, 2021)
Stress can cause various problems that distrupt the life of students and their educational process at the boarding school. This study aims to see the effectiveness of writing a letter of gratitude in reducing stress levels of the students at the Darul Arqam Gombara Islamic Boarding School Makassar. This study is an experimental research used pretest-posttest control group design. The subjects in this study found 14 people (8 people in the experimental group and 6 people in the control group) who were students who indicated experiencing stress. The measuring instrument used in this study is the stress level scale compiled by the researcher, with a reliability value of 0.785. Analysis of the data used is nonparametric analysis with the Mann Whitney U-test method. The results of this study indicate that the intervention of writing a letter of gratitude is effective in reducing stress levels in students. These results can be seen from the significant difference after being given treatment in the experimental group and the control group with a p-value = 0.029 (p <0.05) with a mean of 8.81 for the experimental group and a mean of 4.1 for the control group. As the conclusion, the technique of writing gratitude letters is effective in reducing the stress level of students, so it can be used by students who have high stress levels.